FORECASTING PENGERJAAN BERKAS MENGGUNAKAN METODE ARIMA DAN SARIMA - Paulina Octavia; Eko Sulistyono (LPPM-ITEBA, 2023)
The National Land Agency (BPN) is a non-ministerial government agency in Indonesia which has the task of carrying out governmental tasks in the land sector in accordance with statutory provisions. BPN was formerly known as the Agrarian Office. The formation of the Batam City Land Service is an implementing element of the Batam City Government in the field of Land Affairs which is led by a Head of Service who is under and responsible to the Mayor of Batam. The Batam City National Land Agency always carries out administrative processes starting from Monday to Friday. However, currently the Batam City BPN is serving a